Ministry of vengeance - Maris, Peter; Schneider, John, 1960-; Motion Picture Corporation of America; Cinetel Films ([Los Angeles, CA] : Motion Picture Corporation of America, 1989)
After his innocent wife and daughter are slaughtered by fanatic Lebanese terrorists, a Unitarian minister (Schneider) leaves the church, vowing to avenge his family. With the help of an old Vietnam war buddy he trains for an assault on the terrorist stronghold, but is nearly thwarted by the CIA which is using the terrorists for its own ends.
John Schneider, James Tolkan, Ned Beatty, Apollonia, Yaphet Kotto, George Kennedy.
Director of photography, Mark Morris; editor, Michael Haight; music, Scott Roewe.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 7, 2015)
Keywords: United States. -- Central Intelligence Agency -- Drama; Vietnam War, 1961-1975 -- Veterans -- Drama; Terrorists -- Lebanon -- Drama; Americans -- Lebanon -- Drama; Revenge -- Drama; Action and adventure films; Feature films; Internet videos; Streaming video